(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
Masson’s trichrome (MT) is a three-color staining protocol used in histology. MT allows to show and quantify changes such as tissue repair (healing) and collagen deposition. Also, it can be used to quantify blood vessels, in epithelial dysplasia and squamous cell carcinoma. The objective of this work is to describe the MT staining technique and to exemplify some applications of this technique in routine veterinary histopathological diagnosis. Archived histologic sections were selected from the records of the histopathology laboratory. Tissues were selected in base on theirs structures and lesions that could be evaluated with MT: a rabbit lung with a chronic suppurative bronchopneumonia; a bovine liver with lesions of Echium plantagineum poisoning; and a bovine eyelid with a squamous cell carcinoma. The TM was able to show fibroplasia in the pulmonary interstitium and confirm the presence of a chronic respiratory process, and clearly revealed an abundant fibrovascular tumor stroma, with profuse connective tissue and neovascularization between the tumor cells in deep dermis. In the liver, extensive and marked fibroplasia was confirmed. MT represents a complementary coloration to routine hematoxylin and eosin stain (H&E) and provides accurate information from several pathological processes, mainly those related to fibrovascular proliferation and scarring.